2022
DOI: 10.1007/s00381-021-05400-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of blood product removal in intraventricular hemorrhage of prematurity: a meta-analysis of the clinical evidence

Abstract: Introduction Premature neonates have a high risk of intraventricular hemorrhage (IVH) at birth, the blood products of which activate inflammatory cascades that can cause hydrocephalus and long-term neurological morbidities and sequelae. However, there is no consensus for one treatment strategy. While the mainstay of treatment involves CSF diversion to reduce intracranial pressure, a number of interventions focus on blood product removal at various stages including extraventricular drains (EVD), intra-ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Some studies have shown that there are differences in the expression of some inflammatory indexes in different neurosurgical diseases [ 11 , 12 ]. Detecting these inflammatory indicators can help us quickly identify the types of secondary hydrocephalus, so as to guide our clinicians to take reasonable and effective treatment measures to better improve the quality of life and prognosis of patients [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown that there are differences in the expression of some inflammatory indexes in different neurosurgical diseases [ 11 , 12 ]. Detecting these inflammatory indicators can help us quickly identify the types of secondary hydrocephalus, so as to guide our clinicians to take reasonable and effective treatment measures to better improve the quality of life and prognosis of patients [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Whilst the principles of ventricular lavage in PHVD have remained consistent over time, there has been variation in the techniques proposed to deliver ventricular lavage [ 2 , 19 21 ]. Advantages have been described which favour NEL, for example, allowing direct visualisation of the progress of haematoma removal and therefore enabling targeted irrigation and clot removal under direct vision [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage is that this procedure is often delivered during the time of insertion of a temporising device within the same operative session, avoiding additional risks associated with repeated procedures and sessions under general anaesthetic [19]. With neuro-endoscopic lavage emerging as a feasible and safe technique, technical variation between operating paediatric neurosurgeons exists [18, 19, 20]. Whilst this made the consensus process challenging, the discussion and multiple iterations that arose from the staged consensus process during this study were valuable and relevant.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the principles of ventricular lavage in PHVD have remained consistent over time, there has been variation in the techniques proposed to deliver ventricular lavage [2,[18][19][20]. Advantages have been described which favour NEL, for example, allowing direct visualisation of the progress of haematoma removal and therefore enabling targeted irrigation and clot removal under direct vision [1].…”
Section: Discussionmentioning
confidence: 99%